Multi-Omics-Based Identification and Functional Characterization of Gh_A06G1257 Proves Its Potential Role in Drought Stress Tolerance in Gossypium hirsutum - Mehari, Teame Gereziher; Xu, Yanchao; Umer, Muhammad Jawad; Shiraku, Margaret Linyerera; Hou, Yuqing; Wang, Yuhong; Yu, Shuxun; Zhang, Xianlong; Wang, Kunbo; Cai, Xiaoyan; Zhou, Zhongli; Liu, Fang (Frontiers in Plant Science, 2021)
Cotton is one of the most important fiber crops globally and various abiotic stresses including drought cause yield losses. We used transcriptome profiles to investigate the coexpression patterns of gene networks associated with drought stress tolerance. We identified 3 gene modules containing 3567 genes highly associated with drought stress tolerance. Within these modules, based on intramodular significance we identified 13 hub genes for further validation. Yellow module has five hub genes (Gh_A07G0563, Gh_D05G0221, Gh_A05G3716, Gh_D12G1438, and Gh_D05G0697), brown module contains three hub genes belonging to the ALDH family (Gh_A06G1257, Gh_A06G1256, and Gh_D06G1578), and pink module has five hub genes (Gh_A02G1616, Gh_D12G2599, Gh_D07G2232, Gh_A02G0527, and Gh_D07G0629). Based on RT-qPCR results Gh_A06G1257 gene has the highest expression under drought stress in different plant tissues and it might be the true candidate gene linked to drought stress tolerance in cotton. Silencing of Gh_A06G1257 in cotton leaves conferred significant sensitivity in response to drought stress treatments. Overexpression of Gh_A06G1257 in Arabidopsis also confirms its role in drought stress tolerance. L-valine, Glutaric acid, L-proline, L-Glutamic acid, and L-Tryptophan were found to be the most significant metabolites playing roles in drought stress tolerance. These findings add significantly to existing knowledge of drought stress tolerance mechanisms in cotton.